2018
DOI: 10.1186/s40100-018-0105-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of marine protected areas and macroeconomic environment on meat consumption in SEAFO countries

Abstract: Livestock production and consumption of meat are significant contributors to today's most serious environmental problems and global warming. This paper investigates the role of marine reserves in shaping meat consumption pattern across member countries of the South East Atlantic Fisheries Organisation (SEAFO) for the period 1990 to 2009. Using a panel data including economic factors, life expectancy and environmental awareness, we find that meat consumption is positively associated with the presence of marine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(38 reference statements)
0
0
0
Order By: Relevance
“…Research conducted in Brazil has demonstrated that red meat consumption significantly contributes to lowering carbon emissions [20]. Similarly, studies based in the United States have indicated that meat consumption acts as a detrimental factor impacting terrestrial ecosystems and biodiversity [21]. Consequently, it is recommended to decrease the intake of meat products or substitute such as cattle with poultry alternatives [22].…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted in Brazil has demonstrated that red meat consumption significantly contributes to lowering carbon emissions [20]. Similarly, studies based in the United States have indicated that meat consumption acts as a detrimental factor impacting terrestrial ecosystems and biodiversity [21]. Consequently, it is recommended to decrease the intake of meat products or substitute such as cattle with poultry alternatives [22].…”
Section: Introductionmentioning
confidence: 99%